Ablation threshold and crater morphology of amorphous and crystalline SiO2 glass for extreme ultraviolet femtosecond pulses. (18th November 2020) - Shibuya, T.; Sakaue, K.; Ogawa, H.; Dinh, T.-H.; Satoh, D.; Terasawa, E.; Washio, M.; Tanaka, M.; Higashiguchi, T.; Ishino, M.; Kubota, Y.; Inubushi, Y.; et al.
Abstract: The ablation threshold fluence and crater morphology of amorphous and crystalline SiO2 glass were analyzed in the regime of an extreme ultraviolet femtosecond pulse. Despite the difference between the densities (or optical penetration depths) of amorphous and crystalline SiO2 glass, the ablation threshold fluences and crater morphologies were found to be comparable. In addition, we compared our experimental results at a 10.3 nm wavelength with those in a previous work at a 13.5 nm wavelength. We conclude that the impact of the difference in density or optical penetration depth of several tens of percent on the ablation process is limited.